ESTIMATING SEEING VALUES FROM VARIOUS REFRACTIVE INDEX STRUCTURE PARAMETER MODELS AT MAUNA KEA, HAWAII - Septiadi, Bayu
Astronomical observations require high precision to produce clear and accurate images. For some wavelength ranges, such as radio and visible light, observations can avoid atmospheric contamination, but this does not mean they are without other disturbances. These disturbances arise due to atmospheric turbulence, known as ”seeing,” which causes changes in the positions of celestial objects. This e?ect results in astronomical images becoming blurred or scintillating, reducing the sharpness and clarity of the recorded images. This study aims to find a correlation between atmospheric parameters from ERA5 reanalysis data and observed seeing values. Through an in-depth understanding of the relationship between atmospheric conditions and seeing quality, this research is expected to make significant contributions in identifying and recommending the best locations for astronomical observatories. The results show that the distribution of FWHM seeing values obtained closely aligns with the observed seeing values for the Mauna Kea Observatory area. These findings utilize wind speed data at various altitudes, ranging from 110.9 meters to 32.4 kilometers, which are then incorporated into the structure index parameter function (C2n ) and Fried Parameter (r0).